Stikine River and the Cassiar from Wrangel, Alaska to Telegraph Creek, B.C [electronic resource] - Hudson's Bay Company. British Columbia Transport Service. ([Victoria, B.C.? : s.n., 1912)
Information for big game hunters and tourists and description of the route of the Company's river steamer Port Simpson. Cf. Edwards & Lort. Cover title. Edwards & Lort, Electronic reproduction. Mode of access: Internet. 44